Perceived Discrimination and Reported Trust and Satisfaction with Providers in African Americans: The Jackson Heart Study - Glover, LáShauntá M. (Ethn Dis, 2017)
OBJECTIVES: 1) To examine the association of multiple dimensions of discrimination with reported trust and satisfaction with providers; 2) to report within-group differences among African Americans (AAs). MAIN MEASURES: Measures of perceived discrimination included everyday, lifetime, burden from lifetime discrimination, and stress from discrimination. Outcomes included trust and satisfaction with providers. METHODS: Descriptive cross sectional study. The study population included AAs aged 35 to 84 years from the Jackson Heart Study (JHS) (N=5,301). Poisson regression (PR) was used to quantify the association between perceived discrimination and reported trust and satisfaction with providers before and after controlling for selected characteristics. RESULTS: The mean everyday discrimination score was 2.11 (SD±1.02), and the mean lifetime discrimination score was 2.92 (SD±2.12). High (vs low) levels of everyday discrimination were associated with a 3% reduction in the prevalence of trust in providers (PR .97, 95% CI .96, .99) in all models. In fully-adjusted models, high (vs low) lifetime discrimination was associated with a 4% reduction in the prevalence of trust and satisfaction (PR .96, 95% CI .95, .98). Burden of discrimination was not associated with trust or satisfaction, but stress from discrimination was inversely associated with satisfaction. CONCLUSIONS: The significant association between discrimination and mistrust and dissatisfaction suggests that health care providers should be made aware of AA perceptions of discrimination, which likely affects their levels of trust and satisfaction.